Halal Certification and Trademark for Consumer Protection in Indonesian Micro-Enterprises - Deviana Yuanitasari; Meliza Meliza; Agus Suwandono; Muhammadafefee Assalihee (Fiat Justisia: Jurnal Ilmu Hukum, 2025)
Halal certification and trademark registration are key legal instruments for strengthening consumer trust in Muslim-majority markets such as Indonesia. For micro-enterprises, they function not only as regulatory compliance mechanisms but also as strategic tools for brand differentiation and market expansion. This study examines the legal frameworks governing halal certification under Law No. 33 of 2014 on Halal Product Assurance and trademark protection under Law No. 20 of 2016 on Marks and Geographical Indications, using a normative juridical approach complemented by qualitative interviews with selected micro-entrepreneurs. The findings show that integrating halal certification and trademark registration generates dual consumer trust based on religious assurance and brand authenticity. However, bureaucratic complexity, limited legal literacy, and cost barriers constrain adoption. The study therefore recommends streamlining procedures, strengthening outreach, and providing targeted financial support to promote broader compliance, consumer protection, and inclusive economic growth.